2009
DOI: 10.1111/j.1708-8305.2009.00301.x
|View full text |Cite
|
Sign up to set email alerts
|

Viral Etiology of Acute Respiratory Infections Among Iranian Hajj Pilgrims, 2006

Abstract: According to the results, each of the above-mentioned viruses played a role in the development of respiratory diseases among Iranian pilgrims, with influenza virus as the commonest one. Because influenza vaccine could not prevent respiratory infections in Hajj pilgrims statistically, the possibility of the appearance of new drift variants not included in vaccine and also inappropriate vaccine handling and storage might be considered. So it is also advisable to check if the circulating influenza strains were di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 11 publications
4
57
2
Order By: Relevance
“…17,18 The coverage rate of 89% in 2012 among Australian Hajj pilgrims compares well with the vaccination rate among the Iranian pilgrims (86%-98%) for the last few years, and French (97%) and domestic Saudi pilgrims (94%) for the 2009 Hajj. 7,11,13,19,20 It was higher than among US (63%) and Malaysian (73%) pilgrims. 6,21 A cross-sectional survey conducted several years ago among Asia-Pacific travelers, including Australians, showed that only 3% of Western (ie, those from Australia, New Zealand, Europe, and North America) travelers received influenza vaccine for their trip and 11% received the vaccine in previous years.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…17,18 The coverage rate of 89% in 2012 among Australian Hajj pilgrims compares well with the vaccination rate among the Iranian pilgrims (86%-98%) for the last few years, and French (97%) and domestic Saudi pilgrims (94%) for the 2009 Hajj. 7,11,13,19,20 It was higher than among US (63%) and Malaysian (73%) pilgrims. 6,21 A cross-sectional survey conducted several years ago among Asia-Pacific travelers, including Australians, showed that only 3% of Western (ie, those from Australia, New Zealand, Europe, and North America) travelers received influenza vaccine for their trip and 11% received the vaccine in previous years.…”
Section: Discussioncontrasting
confidence: 49%
“…4,5 Despite this yearly recommendation, influenza vaccine uptake rate among Hajj pilgrims has varied by country and by year (Table 1). [6][7][8][9][10][11][12][13] There are no comprehensive official data on influenza vaccination rate among Australian Hajj pilgrims or other travelers. A prospective study that assessed the incidence and risk factors for acute respiratory illnesses and influenza infections among Australian travelers between August 2007 and January 2010, reported only 49% influenza vaccine uptake prior to their trip to Asia, and only 56% travelers admitted receiving the vaccine in the 3 years before travel.…”
Section: Cohort 2007 27mentioning
confidence: 99%
“…[14,21,23,28,34,35,48]. Five studies conducted between 2005 and 2013 involved French pilgrims [20,24,[44][45][46]; 3 of these conducted by Gautret et al [24,44,46] [24,44,46].…”
Section: Influenza Vaccine Uptakementioning
confidence: 98%
“…Of these, 6 studies reported laboratory-confirmed influenza as an outcome [10,14,16,22,25,33], but only one study found influenza vaccine to be effective in reducing influenza (p < 0.001) [10]. However, meta-analysis of the data from 6 studies which provided both laboratory results by vaccination status [10,14,16,22,25,33] shows that the influenza vaccine was significantly protective against laboratory-confirmed influenza among Hajj pilgrims (RR, 0.56; 95% CI, 0.41-0.75; p < 0.001) (Fig.…”
Section: Influenza Vaccine Effectivenessmentioning
confidence: 99%
See 1 more Smart Citation